2019
DOI: 10.1074/jbc.ra119.008335
|View full text |Cite
|
Sign up to set email alerts
|

The 1.9 Å crystal structure of the extracellular matrix protein Bap1 from Vibrio cholerae provides insights into bacterial biofilm adhesion

Abstract: Growth of the cholera bacterium Vibrio cholerae in a biofilm community contributes to both its pathogenicity and survival in aquatic environmental niches. The major components of V. cholerae biofilms include Vibrio polysaccharide (VPS) and the extracellular matrix proteins RbmA, RbmC, and Bap1. To further elucidate the previously observed overlapping roles of Bap1 and RbmC in biofilm architecture and surface attachment, here we investigated the structural and functional properties of Bap1. Soluble expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Thus, a certain, as-yet-unidentified protein must be closely related to the maintenance of Staphylococcal biofilms. A recent report revealed that both matrix Bap 1 and Rbm C proteins produced by Vibrio cholerae play distinct adhesive roles in its biofilm formation ( Kaus et al, 2019 ). Wrobel et al (2020) have recently reported that two autotransporters of Yersinia ruckeri , which localize to the outer membrane, contribute to biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a certain, as-yet-unidentified protein must be closely related to the maintenance of Staphylococcal biofilms. A recent report revealed that both matrix Bap 1 and Rbm C proteins produced by Vibrio cholerae play distinct adhesive roles in its biofilm formation ( Kaus et al, 2019 ). Wrobel et al (2020) have recently reported that two autotransporters of Yersinia ruckeri , which localize to the outer membrane, contribute to biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…In Vibrio cholerae , the matrix proteins RbmA, RbmC, and Bap1, in addition to Vibrio polysaccharide and nucleic acids, are known as the major components of V. cholerae biofilm ( Fong et al, 2006 ; Fong and Yildiz, 2007 ; Berk et al, 2012 ). Recently, the crystal structure of Bap1 has also been elucidated ( Kaus et al, 2019 ). Thus, some bacterial biofilms are being analyzed at the molecular level to identify their components.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, RmbC has a role in maintaining and stabilizing the biofilm [177]. A study using mutants lacking RbmC and its homolog Bap1 showed a change of colonial morphology and the loss of biofilm formation capacity [177,178]. On the other hand, RbmA controls the structure of the biofilm [9,179].…”
Section: Biofilm Maturationmentioning
confidence: 99%
“…For V. cholerae, the biofilm matrix primarily consists of the long-chain polysaccharide VPS, which is bound by the major matrix protein RbmA (20)(21)(22). Further matrix components are extracellular DNA (23,24), the RbmC protein and several additional matrix proteins whose functions are mostly uncharacterized (25,26), as well as factors used for surface attachment of the cells, including Bap1, FraH, CraA, and MSHA pili (20,(27)(28)(29)(30)(31)(32). During V. cholerae biofilm growth, RbmA is known to be processed by the proteases HapA, PrtV, and IvaP (33,34), yet neither of these proteases is known to play a role in dispersal from abiotic surfaces (35).…”
Section: Introductionmentioning
confidence: 99%